Olhar e ser olhado: desejo e prazer na sala escura de A Rosa Púrpura do Cairo - Pinto, Vinícius Soares (2017)
The comparisons between the filmic projection in the dark room of the movie theater and the act of closing the eyes and beginning to dream approximated the relations between cinema studies and psychoanalysis. Two areas created almost simultaneously, at the end of the nineteenth century, both dealing with subjects, pleasures, desires and image. Starting from this scenario, the problem arises: will it be possible, through a film work, to identify and investigate the motivations that excite the pleasures and desires of the spectator in the dark room of the theater? The present research, using a cut in the work of American director Woody Allen, selected as corpus the film The Purple Rose of Cairo (1985), assuming that the narrative and aesthetics chosen by the director contribute to understanding the associations amidst the world of cinema and the psyche. Therefore, through the film and bibliographical analyzes, this dissertation has as its general objective the search to understand if Allen’s film is able to represent the pleasures and possible desires involved in the spectatorial experience of those who frequent the dark room of the movie theater. Having as specific objectives, the aim to contextualize The Purple Rose of Cairo in Woody Allen’s work, to present other films that dialogue with the subject, to identify the game of gazes between the subjects in the experience of watching a film, and also to deepen the reflection on the possible desires of the spectator when walking through fiction and non-fiction environments. To accomplish these objectives, the dissertation is divided into three chapters: the first devoted to the presentation and critical reading of Allen's film, the comparison between fiction and non-fiction environments, as well as showing other cinematographic works that converse with the theme presented in The Purple Rose of Cairo. In the second chapter, the focus is on the spectatorial experience in the dark room, deepening the possible motivations that draw people into the darkness, the pleasures involved in the act of looking at something or someone and the relationships built between filmic and dreamlike images. Finally, in the last chapter, one speculates on the possible desires of the viewer by experiencing a movie in the dark room of the cinema.